2015
DOI: 10.1093/jhered/esv013
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Subdivision and Variation in Selfing Rates Among Central American Populations of the Mangrove Rivulus, Kryptolebias marmoratus

Abstract: We used 32 polymorphic microsatellite loci to investigate how a mixed-mating system affects population genetic structure in Central American populations (N = 243 individuals) of the killifish Kryptolebias marmoratus (mangrove rivulus), 1 of 2 of the world's only known self-fertilizing vertebrates. Results were also compared with previous microsatellite surveys of Floridian populations of this species. For several populations in Belize and Honduras, population structure and genetic differentiation were pronounc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 45 publications
2
26
1
Order By: Relevance
“…Second, males are typically the result of hermaphrodites that transform into secondary males by ovarian atresia11. Most of the males in natural populations of this kind have been found to have transformed into an early life stage thereby ovarian tissue is typically absent at later life512131415. High levels of inbreeding like those observed in K. marmoratus are considered as maladaptive for a number of reasons like for example susceptibility to diseases1617.…”
mentioning
confidence: 99%
“…Second, males are typically the result of hermaphrodites that transform into secondary males by ovarian atresia11. Most of the males in natural populations of this kind have been found to have transformed into an early life stage thereby ovarian tissue is typically absent at later life512131415. High levels of inbreeding like those observed in K. marmoratus are considered as maladaptive for a number of reasons like for example susceptibility to diseases1617.…”
mentioning
confidence: 99%
“…We found that the different selfing lineages of Kryptolebias hermaphroditus distributed in three sampling sites of northeastern Brazil differed significantly in parasite loads, genetic composition, and DNA methylation patterns, which might indicate specific interactions between host genotypes, epigenotypes, and parasites (Dybdhal & Lively, ; Ebert, ). Previous studies on mangrove killifishes had identified extensive genetic structuring both between (Tatarenkov et al, , ) and within mangrove systems even at close geographical proximity (Ellison et al, ; Tatarenkov, Earley, Taylor, & Avise, ; Tatarenkov et al, ), as a consequence of the self‐fertilizing nature of these fish. We found strong evidence of genetic structuring between sampling sites and selfing lineages using microsatellites, but lower differentiation for AFLP genetic markers (likely due to the different mutation rate of the markers) and epigenetic markers (MS‐AFLPs).…”
Section: Discussionmentioning
confidence: 97%
“…Two recent studies involving microsatellite loci have documented several of these effects for regional assemblages of K . marmoratus populations from the Florida Keys (Tatarenkov et al ., ) and for several sites in Central America (Tatarenkov et al ., ). In both cases, geographic population‐genetic structure was highly statistically significant and arranged in patterns that were marginally consistent with models of isolation by distance.…”
Section: A Brief History Of Population‐genetic Research On Mixed‐matimentioning
confidence: 97%
“…Observed distributions of individual heterozygosities in Central America also showed very good agreement with the distributions expected under an equilibrium mixed‐mating model with the same selfing rates (Fig. ) (Tatarenkov et al ., ). This latter finding suggests that despite pronounced spatial heterogeneity in genotypic frequencies, selfing rates within populations may tend to be rather stable through time.…”
Section: A Brief History Of Population‐genetic Research On Mixed‐matimentioning
confidence: 97%
See 1 more Smart Citation